1980
DOI: 10.1093/nar/8.5.943
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear proteins in Drosophila melanogaster cells after heat shock and their binding to homologous DNA

Abstract: After 5 minutes heat shock at 37 0C Drosophila melanogaster Kc-cell nuclear proteins were extracted with 0.4M NaCl and compared by SDS gel electrophoresis with extracts from cells grown at 250C. Two proteins (39 000 and 46 000) were only found in heat shock nuclei. Reconstitution with total Drosophila DNA or a DNA fragment from the heat inducible locus 87A/C covalently coupled to sepharose was performed. In the presence of calf thymus competitor DNA these proteins and also others of lower molecular weight show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We recently described two proteins (mol wt 46,000 and 40,000) that appear to change their cellular distribution after a 5-min heat shock of D. melanogaster Kc cells (6) . To determine the localization of these proteins within Kc cells, we fractionated cells into nuclear, mitochondrial, microsomal, and soluble cytoplasmic components using differential centrifugation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently described two proteins (mol wt 46,000 and 40,000) that appear to change their cellular distribution after a 5-min heat shock of D. melanogaster Kc cells (6) . To determine the localization of these proteins within Kc cells, we fractionated cells into nuclear, mitochondrial, microsomal, and soluble cytoplasmic components using differential centrifugation.…”
Section: Resultsmentioning
confidence: 99%
“…Cell debris was removed by centrifugation at 10,000 g for 15 min, and this postmitochondrial supernate subjected to a 100,000 gcentrifugation in a SW56 rotor (Beckman Instruments, Inc., Fullerton, Calif.) for 5 h. The pellet is referred to as microsomal fraction whereas the supernate represents the soluble fraction . Nuclei were prepared and extracted with buffered 0.4 M NaCl as described recently (6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for the reported association ofthe small hsps with chromatin and nuclear matrix also comes in part from studies of the 46-kDa IFP. Falkner and Biessmann (33) found that this protein is present in nuclear extracts from heat-shocked cells and will bind to DNA. Thus, any disruption of nuclei (e.g., isolation of chromatin, salt extraction, DNase treatment, or, perhaps, severe heat shock) may allow the IFPs to enter the nucleus, where they can stick to chromosomes and other nuclear structures.…”
mentioning
confidence: 99%